Deep Brain Stimulation Battery Longevity: Comparison of Monopolar Versus Bipolar Stimulation Modes. Issue 4 (9th January 2016) - Almeida, Leonardo; Rawal, Pawan V.; Ditty, Benjamin; Smelser, Bryan L.; Huang, He; Okun, Michael S.; Guthrie, Barton L.; Walker, Harrison C.
Abstract: Background: DBS is an effective treatment for movement disorders, but it is relatively complex, invasive, and costly. Little is known about whether stimulation mode alters pulse generator (battery) longevity in routine clinical care. The aim of this study was to compare battery longevity during monopolar versus bipolar stimulation in patients who underwent DBS for movement disorders. Methods: We evaluated 2, 902 programming adjustments and calculated the average stimulator settings for 393 batteries in 200 unique patients with Parkinson's disease (PD) and essential tremor (ET). We classified the pulse generators into different stimulation modes (monopolar, bipolar, tripolar, and double monopolar) and compared battery longevity with Kaplan–Meier's survival analyses using the log‐rank test. We exclusively implanted the Medtronic 3387 lead with adjacent electrode contacts separated by 1.5 mm. Results: Mean pulse generator longevity was 47.6 ± 1.6 months regardless of diagnosis or stimulation mode. Bipolar stimulation mode was associated with greater longevity than monopolar stimulation (56.1 ± 3.4 vs. 44.2 ± 2.1 months; P = 0.006). This effect was most pronounced when stimulation parameters were at low‐to‐moderate intensity settings. Double monopolar configuration was associated with less pulse generator longevity than conventional stimulation modes (37.8 ± 5.6 vs. 49.7 ± 1.9; P = 0.014). Conclusion: Implanted pulse generators initially programmed in bipolar mode provided 1 year of additional battery longevity versus monopolar mode in this large, retrospective series of patients with ET and PD. Given satisfactory efficacy for motor symptoms, bipolar stimulation mode is a feasible alternative programming strategy at the initiation of DBS therapy.